MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPAS MELALUI MODEL PJBL (PROJECT BASED LEARNING) MENGGUNAKAN MEDIA DIORAMA KELAS V UPTD SD NEGERI 1 TAMAN FAJAR - Ayu Ningrum; Bambang Ariyanto; Sulis Anjarwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the low learning outcomes of fifth-grade students in the Natural and Social Science (IPAS) subject. Therefore, this study aimed to determine the improvement in student learning outcomes through the implementation of the Project-Based Learning (PjBL) model using diorama media in Grade V at UPTD SD Negeri 1 Taman Fajar. The method used was Classroom Action Research (CAR), conducted in two cycles, with each cycle consisting of three meetings. The sampling technique employed was purposive sampling, involving 19 students as research subjects. Data collection techniques included observation, interviews, documentation, and learning outcome tests conducted during the pre-cycle, cycle I, and cycle II stages. The results indicated an improvement in student learning outcomes in each cycle. In the pre-cycle, 9 students (47.37%) achieved mastery with an average score of 70.42, a maximum score of 94, and a minimum score of 58. In cycle I, the number of students who achieved mastery increased to 13 students (68.42%) with an average score of 77.37, a maximum score of 95, and a minimum score of 60. Furthermore, in cycle II, the number of students achieving mastery further increased to 17 students (89.47%) with an average score of 83.55, a maximum score of 95, and a minimum score of 67.5. Consequently, there was an increase in learning mastery from the pre-cycle to cycle II by 42.10%, along with an improvement in the average score by 13.13 score. Based on these results, it can be concluded that the implementation of the Project-Based Learning (PjBL) model with diorama media effectively improves student learning outcomes in the IPAS subject for Grade V at UPTD SD Negeri 1 Taman Fajar.